The Description Of Jumping Spider Genus Rhene Thorell, 1869 (Araneae: Salticidae) In West Sumatra - Ouben, Syatila Baiduri (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2023)
Salticidae has sexual dimorphism where the morphology of male and female is very different (body shape and size) causing misidentification either mistaken for different species or equating male and female morphology. One genus in family Salticidae that has this problem is genus Rhene Thorell, 1869 with a wide distribution area on various countries. This research objectives are to determine the type of genus Rhene’s species found in West Sumatra, how the description of morphology and genitalia, and whether the characteristics of specimens will be the same as specimens in other countries. This research is a descriptive study of spiders of genus Rhene. Hand collecting and beating were applied in sampling from November 1st 2021 to February 28th 2023 in random locations (West Sumatra) with various habitat types. The datas obtained will be compiled into descriptions, illustrations and morphometrics. The result of this research found two species of genus Rhene in West Sumatra, Rhene albigera in Mangguang Mangrove Forest, Pariaman, and Rhene flavigera in Anai Valley Area to Taruko. R. albigera has a simple hair pattern, dominant hair colour is yellow and the head shape tends to be square and the abdomen of female and male is wide. R. flavigera has a complex and dense hair pattern, diverse colour variations (dominantly grey-white), a flatter head shape in an isosceles trapezoid, also a slender male and female abdomen.